Business Feasibility Analysis for MSMEs (Case Study of Arfer Outlet in Palu City) - DEWI, Ayu Kumala; INDRI, Maulana; DIN, Muhammad; MUNAWARAH, Munawarah (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:Micro, Small, and Medium Enterprises (MSMEs) are a crucial component of the Indonesian economy. Their role is crucial, not only as job creators but also as key drivers of the local economy. This study aims to analyze the feasibility of the Arfer Outlet in Palu City as an MSME in the beverage sector.Methodology:The research method uses a qualitative descriptive approach combined with quantitative analysis, focusing on two main aspects: non-financial and financial. The financial aspect is analyzed using five indicators: Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), Internal Rate of Return (IRR), and Average Rate of Return (ARR).Findings:The results of the study indicate that the Arfer Outlet is financially feasible. It is indicated by an NPV value of Rp3,602,691 (positive), a PI of 1.35, an IRR of 48.93%, and an ARR of 85.96%. Although the PP value of 1.16 years slightly exceeds the economic life of the asset, the difference is still within reasonable limits, so the business is still considered feasible.Implication:These findings confirm that financial indicators can provide an objective picture of a business's sustainability prospects. Therefore, this study not only contributes to the literature on business feasibility studies for MSMEs in the beverage sector but also provides practical recommendations for micro-enterprise development in Indonesia.